Harm reduction : national and international perspectives - Inciardi, James A.; Harrison, Lana D. (Sage Publications, 2000)
Harm reduction programmes accept the reality of drug use while attempting to reduce its harmful consequences to individuals and society. Here, contributors discuss the philosophical basis and history of such policies and examine their outcomes.